Incidence of hemidiaphragmatic paresis after peripheral nerve stimulator versus ultrasound guided interscalene brachial plexus block - Poonam Sachin Ghodki; Noopur Dasmit Singh (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: We compared interscalene brachial plexus block (ISBPB) using peripheral nerve stimulation (PNS) and ultrasound (US) techniques. The primary outcomes were the incidence of hemidiaphragmatic paresis (HDP) and the duration of the block. Secondary outcomes were the block success rate, time to conduct the block, onset of sensory block, and dermatomal spread, postoperative pain by Numeric Rating Scale (NRS), duration of postoperative analgesia and incidence of complications. Material and Methods: We conducted a prospective, randomized, and observer-blinded study in 60 patients undergoing shoulder arthroscopy under block plus general anesthesia. ISBPB was performed with 10 ml of 0.5% bupivacaine using either PNS (Group PNS, n = 30) or US (Group US, n = 30). Hemidiaphragmatic function, the primary outcome, was assessed by ultrasonographic evaluation of diaphragmatic movement and pulmonary function tests using a bedside spirometer (forced vital capacity, forced expiratory volume in 1 s and peak expiratory flow rate). General anesthesia was administered to all the patients for surgery. P < 0.05 test was considered to be statistically significant. Results: Twelve patients in Group PNS had HDP and none in Group US (P < 0.0001). PFTs were also significantly reduced in Group PNS (P < 0.0001). The time to conduct the block and sensory onset time both were less in Group US (P < 0.05). The groups did not differ in block success rate, duration of analgesia, and NRS. Other complications like incidence of Horner's syndrome and vascular puncture were comparable in both the groups. Conclusions: PNS guided ISBPB with 10 ml of 0.5% bupivacaine is associated with a higher incidence of HDP as compared to US guided ISBPB. There is no significant difference in quality or duration of analgesia in the two groups.